Community Satisfaction with the SEPEKAN System at Bappeda Service Quality Gresik Regency - Ahmad Azharuddin; Hidayat Hidayat; Yanuar Pandu Negoro (Fakultas Teknik, 2023)
Service Quality which is provided by the Regional Development Planning Agency (Bappeda) of Gresik Regency. Service quality is considered a crucial element in carrying out public service functions. This research focuses on analyzing Aspects of quality of service such as reliability, responsiveness, security, empathy, and physical aspects. The research method used is a case study approach with a qualitative approach. Data was obtained through direct observation and interviews with staff and consumers on the SEPEKAN System service at Bappeda and related parties. The data is carefully analyzed to identify the extent of the current quality of service. The results of the study illustrate the general picture of the quality of services provided by Bappeda Gresik Regency including the highest level of importance, namely the X8 attribute regarding the fairness of costs/tariffs in services with a value of 3,708. The dimension of service quality that most affects community satisfaction in the SEPEKAN Bappeda System of Gresik Regency is the dimension of Responsiveness with a gap level of 0.169, which is an attribute of the speed of time in providing services. These findings have important implications for relevant parties in identifying areas of improvement and developing policies to improve the quality of public services in the future. It is hoped that this research can make a positive contribution to efforts to improve better public services in the regions.